Role of Resistant Starch in Improving Gut Health, Adiposity, and Insulin Resistance - Keenan, Michael J; Zhou, June; Hegsted, Maren; Pelkman, Christine; Durham, Holiday A; Coulon, Diana B; Martin, Roy J (Advances in food and nutrition research, 2015)
The realization that low–glycemic index diets were formulated using resistant starch led to more than a decade of research on the health effects of resistant starch. Determination of the metabolizable energy of the resistant starch product allowed for the performance of isocaloric studies. Fermentation of resistant starch in rodent studies results in what appears to be a healthier gut, demonstrated by increased amounts of short-chain fatty acids, an apparent positive change in the microbiota, and increased gene expression for gene products involved in normal healthy proliferation and apoptosis of potential cancer cells. Additionally, consumption of resistant starch was associated with reduced abdominal fat and improved insulin sensitivity. Increased serum glucagon-like peptide 1 (GLP-1) likely plays a role in promoting these health benefits. One rodent study that did not use isocaloric diets demonstrated that the use of resistant starch at 8% of the weight of the diet reduced body fat. This appears to be approximately equivalent to the human fiber requirement. In human subjects, insulin sensitivity is increased with the feeding of resistant starch. However, only 1 of several studies reports an increase in serum GLP-1 associated with resistant starch added to the diet. This means that other mechanisms, such as increased intestinal gluconeogenesis or increased adiponectin, may be involved in the promotion of improved insulin sensitivity. Future research may confirm that there will be improved health if human individuals consume the requirement for dietary fiber and a large amount of the fiber is fermentable.